2019
DOI: 10.1103/physrevb.100.125120
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic response of Sr2RuO4 : Quasi-local spin fluctuations due to Hund's coupling

Abstract: We study the magnetic susceptibility in the normal state of Sr2RuO4 using dynamical mean-field theory including dynamical vertex corrections. Besides the well known incommensurate response, our calculations yield quasi-local spin fluctuations which are broad in momentum and centered around the Γ point, in agreement with recent inelastic neutron scattering experiments [P. Steffens, et al., Phys. Rev. Lett. 122, 047004 (2019)]. We show that these quasi-local fluctuations are controlled by the Hund's coupling an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 86 publications
8
40
0
Order By: Relevance
“…All techniques find almost temperature-independent quasiferromagnetic excitations in pure Sr 2 RuO 4 . This ferromagnetic response agrees qualitatively with a recent dynamical mean-field theory (DMFT) analysis of magnetic fluctuations [57], which finds essentially local magnetic fluctuations superposed on the well-known nesting signal. However, the neutron data disagree with a fully local character as they show a finite q dependence [45].…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…All techniques find almost temperature-independent quasiferromagnetic excitations in pure Sr 2 RuO 4 . This ferromagnetic response agrees qualitatively with a recent dynamical mean-field theory (DMFT) analysis of magnetic fluctuations [57], which finds essentially local magnetic fluctuations superposed on the well-known nesting signal. However, the neutron data disagree with a fully local character as they show a finite q dependence [45].…”
Section: Introductionsupporting
confidence: 88%
“…We wished to extend this study focusing on the q dependence of the magnetic quasiferromagnetic response. Recent DMFT calculations [57] find evidence for local fluctuations superposing the well-established nesting excitations, which agree qualitatively with the experimental quasiferromagnetic signal. However, while the neutron experiments indicate a finite suppression of the quasiferromagnetic response toward the boundaries of the Brillouin zone, the DMFT calculation obtains an essentially local feature without such a q dependence.…”
Section: Shape Of the Quasiferromagnetic Fluctuationssupporting
confidence: 76%
“…[15]. While recent neutron scattering experiments and DMFT calculations do not support ferromagnetic spin fluctuations giving rise to spin-triplet pairing [42,43], this triplet leads to an anisotropy, but cannot reproduce the >50% drop in the NMR response, with an ∼40% or smaller drop in the NMR response for all field strengths, unlike the OSST pairing. For this odd-parity pairing, the drop in the Knight shift with no SOC is 50%, and the inclusion of SOC decreases the magnitude of the drop.…”
mentioning
confidence: 99%
“…By using DFT, we have a well defined Fermi liquid which allows us to study the role of SOC but neglects strong electronic correlations at the one-body level. Although various works have shown their importance for SRO [39][40][41][42][43][44], none of them was able to correctly account for electronic correlations, SOC and temperatures below T FL at the same time. The exactitude of SRO's normal state in its Fermi liquid regime is an ongoing challenge.…”
Section: Normal State Electronic Structurementioning
confidence: 99%
“…It depends on two parameters: on-site Coulomb repulsion U and Hund's coupling J. In SRO, works based on realistic electronic structures have shown that strong electronic correlations improve considerably the quantitative description of the one-and twobody propagators characterizing its normal state [39][40][41][42][43][44]. In this work, we include strong electronic correlations only at the two-body level through spin and charge fluctuation theory described in Sec.…”
Section: Normal State Electronic Structurementioning
confidence: 99%